Design and Simulation of a Fused Silica Space Cell Culture and Observation Cavity with Microfluidic and Temperature Controlling - Shangchun Fan; Jinhao Sun; Weiwei Xing; Cheng Li; Dongxue Wang (Journal of Applied Mathematics)
We report a principle prototype of space animal cell perfusion culture and observation. Unlike previous work, our cell culture system cannot only realize microfluidic and temperature controlling, automatic observation, and recording but also meet an increasing cell culture at large scale operation and overcome shear force for animal cells. A key component in the system is ingenious structural fused silica cell culture cavity with the wedge-shaped connection. Finite volume method (FVM) is applied to calculate its multipoint flow field, pressure field, axial velocity, tangential velocity, and radial velocity. In order to provide appropriate flow rate, temperature, and shear force for space animal cell culture, a closed-loop microfluidic circuit and proportional, integrating, and differentiation (PID) algorithm are employed. This paper also illustrates system architecture and operating method of the principle prototype. The dynamic culture, autofocus observation, and recording of M763 cells are performed successfully within 72 h in the laboratory environment. This research can provide a reference for space flight mission that carries an apparatus with similar functions.